Cerebrospinal Fluid Biomarkers in Multiple System Atrophy Relative to Parkinson's Disease: A Meta-Analysis. (31st May 2021) - Xie, Dan; Feng, Ling; Huang, Hongyan; Zhao, Quanzhen; Ning, Pingping; Shen, Qiuyan; Lu, Haitao; Xu, Fang; Xu, Yanming
Abstract : Objective . To investigate the differences of candidate cerebrospinal fluid (CSF) biomarkers associated with multiple system atrophy (MSA) and Parkinson's disease (PD). Method . Here, a systematic review and meta-analysis were conducted on studies related to CSF biomarkers associated with MSA and PD obtained from PubMed, Web of Science, Embase, and Cochrane databases. Data were pooled where appropriate and used to calculate standardized mean differences (SMDs) with 95% confidence intervals (CI). Heterogeneity was assessed using the I 2 statistic while Egger's test was used to test for existing publication bias. Results . MSA patients had higher CSF t-tau (SMD = 0.41, 95% CI: 0.10 to 0.72) and YKL-40 (SMD = 0.63, 95% CI 0.12 to1.15) as well as DJ-1 (SMD = 1.05, 95% CI 0.67 to 1.42) levels than PD patients, while CSF p-tau (SMD = − 0.17, 95% CI, -0.31 to -0.02) and A β -42 (SMD = − 0.33, 95% CI, -0.55 to -0.12) levels in MSA patients were lower than those in PD patients. There were no differences in CSF's GFAP and Flt3 ligand levels in both MSA and PD patients. Conclusion . The study revealed the differences in CSF biomarker levels between MSA and PD cohorts that can be further explored to clinically distinguish MSA from PD.